PENGARUH PELATIHAN TERHADAP KINERJA KARYAWAN PADA DIVISI PELAYANAN SUMBER DAYA MANUSIA PT. POS INDONESIA (PERSERO) BANDUNG - Havivahani Pertiwi; Bachruddin Saleh Luturlean (Almana : Jurnal Manajemen dan Bisnis, 2019)
Employees of PT. Pos Indonesia, the human resources service division has a different level of knowledge and skills. This can affect the results of employee performance in the division. The purpose of this study was to understand and analyze the effect of training on the performance of employees of the human resources service division of PT. Pos Indonesia (Persero) Bandung. The method used in this study is descriptive and quantitative causality analysis methods. The data analysis technique used is a simple linear regression analysis. This study uses sources from primary data as well as collecting research data using questionnaires and interviews. The sample from this study were 35 employees of PT. Pos Indonesia (Persero) Bandung division of human resources services using saturated sampling techniques. The results of this study indicate that training has an influence on the performance of the human resources service division of PT. Pos Indonesia (Persero) Bandung. The coefficient of determination (R Square) shows a value of 0.3249 or 32.49%. This means that training variables have an influence on the performance variables of 32.49% and the remaining 67.51% are influenced by other variables not examined.